Genetic analysis of resistance to post flowering stalk rot in tropical germplasm of maize (Zea mays L.). (April 2018) - Mir, Z.R.; Singh, P.K.; Zaidi, P.H.; Vinayan, M.T.; Sharma, S.S.; Krishna, M.K.; Vemula, A.K.; Rathore, A.; Nair, S.K.
Abstract: Post flowering stalk rot (PFSR) is one of the major biotic constraints to maize production in tropical and sub-tropical environments. It is a complex disease caused by multiple pathogens, among which Fusarium moniliforme and Macrophomina phaseolina are the major ones that cause severe yield losses in the Asian tropics. A set of maize inbred lines was evaluated at two locations for Fusarium stalk rot (FSR) and Macrophomina stalk rot (MSR). Based on line evaluation trials, resistant and susceptible lines were selected and crossed following a Diallel mating design IV to study the gene action for resistance to these stalk rots and the estimating the combining ability of inbred lines. A 9 × 9 diallel (Diallel-A) produced 36 hybrids for studying FSR resistance, and a 12 × 12 diallel (Diallel-B) produced 66 hybrids to analyse the resistance towards both FSR and MSR. These hybrids were evaluated at two locations for MSR and one location for FSR with artificial inoculation. The hybrids differed significantly for FSR (p < 0.05), as was the general combining ability (GCA) effects (p < 0.01), while Specific combining ability (SCA) effects were found to be non-significant. The analysis of the trials under MSR, showed significant difference for GCA, SCA, GCA × environment (p < 0.01), and hybrid × environment (p < 0.05) while SCA × environment was non-significant. The Baker ratio, which shows the relative importance of GCA over SCA, was close to unity for both the stalk rots, and hence a predominant additive gene effect was inferred towards resistance to these diseases. Though the GCA × environment interaction was significant for MSR, this study identified lines and their cross combinations with high resistance and large GCA and SCA effects across environments for FSR and MSR This offers scope for source population improvement for resistance to these stalk rots, as well as developing maize hybrids with stable resistance to Post flowering stalk rot. Highlights: Our research is based on host-plant resistance and inheritance pattern of post flowering stalk rots in tropical maize germplasm. We developed two half-diallel crosses, A and B to study the inheritance of resistance for Fusarium stalk rot (FSR) and Macrophomina stalk rot (MSR). A 9 × 9 half-diallel (Diallel-A) produced 36 hybrids to analyse combining ability for FSR resistance. Another 12 × 12 half-diallel (Diallel-B) produced 66 hybrids to analyze combining ability for resistance to both FSR and MSR. Mean square of General combining ability (GCA) effects to the total genetic effect were close to unity for both FSR and MSR, indicating that resistance is predominantly governed by additive gene action. Our experiments identified inbred lines VL1017256 and VL107730 exhibited favourable GCA effects for FSR and MSR resistance, respectively. Hybrid VL1017256 × VL1018172 and SNL142789 × VL1018142 at Hyderabad showed high resistance for FSR. Hybrid VL107730 × VL0511321 showed high resistance for MSR at both the locations-Hyderabad and Ludhiana.